Investigation of Drilling Parameters Affecting Borehole Circularity in Cortical Bone - Dityamri, Arzaq Guruh; Ibrahim, Gusri Akhyar; Harun, Suryadiwansa; Burhanuddin, Yanuar (Universitas Muhammadiyah Jakarta, 2024)
Cortical bone drilling is a critical step performed prior to implant bolt placement, where drilling parameters play a significant role in the success of the procedure. This study investigates the effects of rotational speed, feed rate, and cooling fluid type on the outcome of the drilling process. A Box-Behnken experimental design was employed, involving 15 samples. Drilling operations were conducted using an SS316L drill bit on a 3-axis CNC machine. Circularity was analyzed using a Mitutoyo PJ3000 profile projector by measuring the x- and y-axis lines of the drill hole shadows under projector illumination. Hardness testing of bone specimens revealed an average microhardness of 45.48 HV with a standard deviation of 1.74, indicating their suitability as a human bone model. The lowest circularity value, 0.00125, was achieved at a rotational speed of 1,500 rpm, a feed rate of 60 mm/min, and in the absence of coolant. ANOVA results show that the feed rate (Vf) significantly affects circularity compared to rotational speed (V) and coolant, with a P-value of 0.0126 and an F-value of 8.86. These findings provide insights for optimizing cortical bone drilling procedures in biomedical applications. Future research should explore temperature distribution across the specimen and drill bit wear resistance resulting from the drilling process.